Galeri, Arsip, Perpustakaan Di Dinas Perpustakaan Dan Kearsipan Daerah Provinsi Di Jawa - Rochani Rahayu; Yupi Royani (Jurnal Gema Pustakawan, 2021)
The research was conducted using descriptive methods, on six Badan Perpustakaan dan Arsip Daerah (DPAD) in Java. The purpose of this research is to find out the types of library services, archives, galleries and also the hours of service each week. Data was collected from each DPAD site, while the data collected included library services, archive services, galleries, and service opening hours. The results show that the library services provided are information retrieval, document provision, mobile library, book delivery services. Archive services are archive browsing, archive storage, and restoration of damaged archives. Each DPAD has a gallery, both in the form of real and virtual rooms. The earliest service time is held by the Central Java Archives and Library Service, and the Banten Provincial Library and Archives Service at 07.00 WIB, and at the latest held by the DIY Provincial Library and Archives Service. that is at 22.00 WIB. Based on the results and discussion, it can be concluded that the Provincial Library and Archives Service in Java has been doing what is called the Gallery, Library, and Archive for a long time. The three elements of public service have been carried out well. The longest service time is held by the DIY Provincial Library and Archives Service (86 hours/week). As for the management of government-owned museums, it seems that they have not been unified, but it is possible that due to regional autonomy, the management can be unified, especially at the provincial level.